Eskatologi dalam Perspektif Alkitabiah: Pemahaman tentang akhir zaman dan kedatangan-Nya yang kedua kali - Lisdayanti Tinambunan; Riri Handriani; Rike Yulianingsih; Rendy Mirianto; Sarmauli Sarmauli (Pusat Riset dan Inovasi Nasional, 2024)
The issue of the second coming of Christ has become a church struggle but is also difficult to understand in the Bible. Because the second coming of Christ is a mystery, which until now has been the subject of theological struggle that has never stopped. Therefore, the meaning of the Parousia can add to the understanding of the end times. This research is a qualitative research, using the literature study method. This research aims to explain the understanding of the end times and His Second Coming in a Biblical Perspective.